Sammenhengen mellom depresjon, mental helse og fysisk funksjon i en alderspsykiatrisk avdeling, en pilotstudie - Aarseth, Elfrid Margrete; Korsnes, Maria Stylianou; Ulstein, Ingun Dina; Tjernæs, Inger-Marie; Mcpherson, Bodil A. (Nordisk Tidsskrift for Helseforskning, 2015)
Patients with mental disorders are often less active than the general population and inactivity over time reduces mental and physical health. We know from previous studies that physical activity contributes to improved mental and physical health, but it is not clear whether any type of physical activity will give the same effect. The objective of this pilot study was to investigate whether the nature of the physical activity the patients participated in during their stay in a psychiatric ward would make a difference in outcome related to improved mental and physical health. Fifty patients (39 women) participated, mean age 80 years (SD 6.0), length of stat from 3 to 28 weeks (mean 8.8, SD 4.4). Patients were offered different types of physical activity and physical therapy in addition to cognitive psychotherapy and supporting conversations. They were subsequently divided into three groups (self-training, joint exercise, regular walking). We examined the difference in treatment effect with regard to general mental health, depression, balance, physical strength and walking skills. Average values showed significant improvements on all tests except for the timed walking tests. Depression scores according to the MADRS was at least one category lower on discharge than on arrival for 31 of the 36 participants. We find that older patients with moderate to severe depression benefit greatly from the treatment they receive during their stay at the age psychiatric ward. The improvements are significant both for mental and physical health. Furthermore, the findings indicate that walking appears to be a type of activity that has especially good effect on mental health.